Tribology Engineering : Selected, Peer Reviewed Papers from the International Conference on Engineering Tribology Technology 2014 (ICETT 2014), November 21-23, 2014, Nantou, Taiwan - Hwang, Yunn-Lin; Horng, Jeng-Haur; Wei, Chin-Chung (Key engineering materials, 2015)
Collection of selected, peer reviewed papers from the International Conference on Engineering Tribology Technology 2014 (ICETT 2014), November 21-23, 2014, Nantou, Taiwan.